Formal but less equal: Gender wage gaps in formal and informal jobs in Brazil - Sarra Ben Yahmed (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In developing countries, a large share of employees work informally and are not covered by employment protection legislation. I study here how gender wage inequality differs across formal and informal jobs in Brazil. The raw gender wage gap is higher in informal jobs (13%) compared to formal jobs (5%), but I show that this difference is an artefact of different male and female selection processes. First, women have better observable characteristics than men and the female advantage is stronger among formal employees. Second, men and women entering formal and informal jobs have different unobservable characteristics. Controlling for endogenous selection into formal vs. informal jobs, I find that the gender gap in wage offers is high and increases with education in formal jobs. In informal jobs, however, estimated wage offers are the same for men and women. I discuss the potential implications of these findings regarding the effect of labour market regulation on gender wage gaps.
urn:nbn:de:bsz:180-madoc-417883
Keywords: J31; O17; 330; gender wage gaps; informality; selection into work statuses; Brazil